1943
DOI: 10.2307/1929698
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Upstream Migration of the Pink Salmon (Oncorhynchus Gorbuscha)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1961
1961
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Previous studies, including ones conducted in Auke Creek, have examined environmental variables as the main factors driving the timing of upstream salmonid migrations (Davidson, Vaughan & Hutchinson, ; Fukushima & Smoker, ; Bond & Quinn, ). Altered environmental conditions (e.g., earlier peak temperature) are often suspected to decouple synchrony between consumer phenology and periods of prey resource abundance (Visser & Both, ; Scheuerell, Zabel & Sandford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, including ones conducted in Auke Creek, have examined environmental variables as the main factors driving the timing of upstream salmonid migrations (Davidson, Vaughan & Hutchinson, ; Fukushima & Smoker, ; Bond & Quinn, ). Altered environmental conditions (e.g., earlier peak temperature) are often suspected to decouple synchrony between consumer phenology and periods of prey resource abundance (Visser & Both, ; Scheuerell, Zabel & Sandford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Very high water discharges can decrease (Jonsson & Jonsson, 2002;, and even temporarily halt upstream fish migrations (Davidson et al, 1943;Sörensen, 1951;Stuart, 1957;Jensen et al, 1989a). For instance, in the River Mistassini, Quebec, Trepanier et al (1996) found that the ascent of landlocked S. salar correlated negatively with water flow, suggesting that the fish preferred falling water phases for ascent.…”
Section: Discharge Is a Controllermentioning
confidence: 99%
“…' [p. 355]. Similarly, pink salmon in southeast Alaska tends to move into freshwater as coherent schools (Davidson et al 1943). Moreover, movement of salmon into streams for spawning can occur in strong 'pulses' of fish entering at once, even in the absence of obvious environmental stimuli to catalyse the pulses, like increases in flow (e.g.…”
Section: Schooling During Upstream Migrationmentioning
confidence: 99%